IN VITRO STUDY OF ANTIMICROBIAL PROPERTIES OF TINOSPORA CORDIFOLIA (GUDUCHI) - DR. HANMANT AMANE,; DR. SHILPA KAORE,; DR. NAVINCHANDRA KAORE, (International Journal of Pharma and Bio Sciences, 2014)
The aim of the present study was to evaluate the antimicrobial activity of Tinospora cordifolia extracts against three standard ATCC strains of Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa. The efficacy of extract was measured in terms of Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC) and zone of inhibition (mm). Antimicrobial activity of aqueous as well as ethanolic extracts were tested in vitro using standard microbroth dilution method with double dilution, against ATCC strains of E.coli, Staphylococcus aureus and Pseudomonas aeruginosa for determination of MIC. MBC values were determined by subculture on standard solid media. The Kirby Bruer’s Disk Diffusion Method was then used to observe the zones of inhibition to a range of concentration at MIC values with other broad spectrum antibiotics. Both aqueous and ethanolic extract of Tinospora cordifolia showed activity against standard ATCC strains of E.coli, Staphylococcus aureus and Pseudomonas aeruginosa in vitro at very high concentrations. Further studies are required to explore the antimicrobial efficacy of Tinospora cordifolia against clinical isolates.